Negation in Bisha Arabic - Alharthy, Fatema Modaf; Ali Alsairi, Meshari; Ali, Jamal Kaid Mohammad (Dirasat: Human and Social Sciences, 2025)
Objectives: Previous studies have provided an analytical description of the phenomenon of negation in Modern Standard Arabic and some other Arabic dialects. In contrast, the phenomenon of negation in the Bishah Arabic dialect has not been described or linguistically analyzed within the framework of Lexical Functional Grammar or any other theory. Therefore, the current research aims to describe and analyze the fundamentals of negation rules in the Bishah Arabic dialect. Research Methods: A descriptive approach was adopted to analyze elements of negation within the framework of Lexical Functional Grammar. The data set was constructed by the authors, who are native speakers of Bishah Arabic. Results: The study found that Bishah Arabic has its own methods and tools for expressing negation. It was observed that negation tools are assigned within field I of the analytical sentence structure. Conclusions: The research concluded that Bishah Arabic is similar to other Arabic dialects in how it expresses negation but possesses unique tools to express the meaning that contradicts reality.